Pengaruh Strategi Bisnis Terhadap Sistem Pengendalian Manajemen – Studi pada BUMN Kategori Industri Strategis di Indonesia - Karsam Karsam (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
The objective of this study is to investigate the influence of business strategy for management control system. The study was carried out on twelve state-owned enterprises strategic industries (BUMNIS) in Indonesia between 2015 and 2016. The studied BUMNIS were selected based on criteria. The data was collected from questionaires that filled by top managements, the board of directors and internal control unit staff. In total, there were sixty respondents and 100% respondent rate. Structural Equation Modelling (SEM) with PLS approach was used to analysis the survey results. This study demonstrates that business strategy has an impact on management control systems of studied BUMNIS.